Quantum Services Engineering: development, quality, testing, and security (Q-SERV Project) - Moguel, Enrique; Garcia-Alonso, Jose; Terres-Escudero, Erik B.; Arias, Danel; Bringas, Pablo García; Muñoz, Ana Díaz; Monje, Moisés Rodríguez; Lama, Jesús Ramón Oviedo; Murillo, Juan M. (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE), 2024)
The new and revolutionary quantum computation aims to advance in important fields such as AI, cybersecurity, and medicine. The development of this technology has encouraged several research centers and companies such as Amazon, IBM, Google or Microsoft to devote considerable efforts to the development of new technologies that bring quantum computing to the market. Currently, access to this technology is provided through the Infrastructure as a Service paradigm and with hybrid systems that combine classical and quantum computing. In order to create these systems, significant advances in serviceoriented quantum computing are required to enable developers to create and operate quantum services with the same level of quality and security as their classical counterparts. Therefore, the project presented in this paper is primarily aimed at providing techniques and methodologies for quantum software development by applying the lessons learned from classical software engineering.